The EU Energy Policy From the Perspective of an EU Candidate Country: The Republic of Serbia - Vlajkovic, Marija (Maastricht 30: A Central European Perspective, 2025)
The EU energy policy framework, apart from being one of the most complex policy and regulatory endeavours under the EU competences also has a wide outreach outside the territory of the Union. The reason behind this wide territorial scope of implementation is the Union external action, mostly that under the enlargement policy. By using a case-study approach, we focus on the external component of the energy policy framework from the perspective of the Republic of Serbia, a candidate country for Union membership and a member to the Energy Community, in order to demonstrate the implications these policy and regulatory measures have on the reform processes of states outside the territorial scope of their validity and implementation. Conversely, by applying longitudinal analysis together with a comparative method we strive to examine the effect the enlargement policy has on the development ofthe EU energy policy considering that its effectiveness, as a policy mechanism regulating network infrastructures, is highly dependent on partnerships with immediate neighbouring countries and with the countries where primary energy sources are located. Finally, we aim to provide an overview of the EU energy policy evolution and a multi-sectorial outline of the said policy’s impact in the Republic of Serbia, putting an accent on the current harmonization challenges.Keywords: EU energy policy, Energy Law, the Energy Community, Serbia